47.4k views
5 votes

{2}^(x + 2) = 9 * ( {2}^(x) ) - 2
How is this solved pls


1 Answer

3 votes

Answer:


x = 1 - log_(2)(5)

Explanation:


{2}^(x + 2) = 9 ( {2}^(x) ) - 2

Using the rules of indices

That's


{x}^(a + b) = {x}^(a) * {x}^(b)

So we have


{2}^(x + 2) = {2}^(x) * {2}^(2) = 4( {2}^(x) )

So we have


4( {2}^(x)) = 9( {2}^(x) ) - 2

Let


{2}^(x) = y

We have

4y = 9y - 2

4y - 9y = - 2

- 5y = - 2

Divide both sides by - 5


y = (2)/(5)

But


{2}^(x) = (2)/(5)

Take logarithm to base 2 to both sides

That's


log_(2)( {2}^(x) ) = log_(2)( (2)/(5) )


log_(2)(2) ^(x) = x log_(2)(2)


log_(2)(2) = 1

So we have


x = log_(2)( (2)/(5) )

Using the rules of logarithms

That's


log( (x)/(y) ) = log(x) - log(y)

Rewrite the expression

That's


x = log_(2)(2) - log_(2)(5)

But


log_(2)(2) = 1

So we have the final answer as


x = 1 - log_(2)(5)

Hope this helps you

User Amacleod
by
5.3k points